The processes of teaching-learning in the inclusive schools (Journal of Parents and Teachers, 2012)
This author highlights that the learning process has to change and be organize in a way in which classrooms, experiences, resources, procedimental processes encourage students to study and no the other way around.
Keywords: Learning processes; experiences; class.; Inclusive education